Hard Algebra Problem

2y= (a^x) + (a^-x), where a>1 and x>0,


prove that (a^x)= y + sqr root (y^2) - 1




similarly, if 2z=(a^3x) + (a^-3x) ,

prove that z= 4(y^3) - 3y

Comments for Hard Algebra Problem

Average Rating starstarstarstarstar

Click here to add your own comments

May 27, 2011
Rating
starstarstarstarstar
Answer is...
by: Aimee

Answer can be viewed here:

#maths #solution on Twitpic

Click here to add your own comments

Join in and write your own page! It's easy to do. How? Simply click here to return to math help forum.